KARAKTERISTIK DAN POLA PERJALANAN WISATAWAN BACKPACKER YANG MENGINAP DI CANGGU, BADUNG - Suprani Gama, Cening; Sudana, I Putu; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Canggu is one of the the most visited areas by backpacker tourists viewed by the amount of hostel accommodations. This study aims to determine the characteristics and travel patterns of backpacker tourists who stay in Canggu. The sample of this research is backpacker tourists staying at Canggu, determining the sample using purposive and quota sampling on 132 respondents. Data obtained in several ways, such as: observation, questionnaires, literature study, and documentation. Quantitative descriptive and qualitative descriptive were used to analyse the data result. The results showed that backpacker tourists take an intra-destination travel pattern, which is to travel in Bali, the most visited tourist destination in Bali is Ubud with an average stay of 6 days, dominantly making an intra-destination travel pattern; Ubud-Uluwatu- Canggu, and Kuta as the first tourist destination visited in Bali. Inter-destination travel patterns, while travel between destinations in Indonesia, most backpacker tourists visit Gili Island with an average stay of 5 days, dominantly doing inter-destination travel patterns such as Gili Island-Bali, and Bali as a tourist destination first visited. Intra-regional patterns, as trips made in Southeast Asian countries, Thailand was most visited by backpacker tourists other than Indonesia, dominantly carried out intra-regional travel patterns like Thailand-Cambodia-Vietnam-Indonesia, and Indonesia as first destination visited. Inter-regional patterns, backpacker tourists also visit other countries other than Southeast Asia, and predominantly visit Australia with an average stay of 91 days, and do inter-regional travel patterns that is Australia- ASEAN, and the ASEAN region being the first destination visited.